SCfM_Prod: A software product certification model - Jamaiah, Haji Yahaya; Deraman, Aziz; Hamdan, Abdul Razak (IEEE Xplore, 2010)
In recent years, there has been an increasing interest in software development and ICT as they become a central issue for business surviving. Companies and software houses are competing to produce software which are claimed to be good and fulfil user's expectation. Therefore, quality aspect of a software product has seen as an important issue but companies that develop the software could not justify and guarantee the quality of their products, thus leaving users in uncertainties. Previous studies have indicated that assessment and certification by an independent assessor may help determining confident in the product. The certification reports are beneficial not only to the users and stakeholders but also to the developers and suppliers. This research proposes a software certification model by end product quality approach or SCfM_Prod. It is an alternative approach to monitor and guarantee level of quality of a software product. This model consists of four main entities: pragmatic quality factor (PQF), assessment team, certification representation method and repository. This paper explains in detail of this model.